APLIKASI TANK MODEL DAN KESEIMBANGAN NERACA AIR STUDI KASUS MODEL DAS MIKRO (MDM),SUB-DAS CISAMPORA, DAS CIMANUK, KABUPATEN MAJALENGKA PROVINSI JAWA BARAT - Syampadzi Nurroh dan Nana Mulyana Arifjaya (Universitas Gadjah Mada, 2015)
The influence of forest cover in landuse is an important concern in the goverment’s regulation for distributionof water flow into the rivers. The River flow is one of the hydrology paramater importantness in order to bepriority in managamenet environmental. The one of hydrology which could be used for water balancepredictionbyTank Model. The Tank Model was applied using daily rainfall, evapotranspiration, and discharge river. Basedon research results that water balance are calculated by input parameter (precipitation, 678 mm) with outputparameter by discharge (623,48 mm) inequation curve discharge(Q = 1,606 (TMA1, 494)) with the correlation (R2)is 0,993and evapotranspiration (631,04 mm). Based on the indicators of the reliability of the Tank model thatthe value of the correlation coefficient (R) of 0,84 can be presented the results of verification in this case quitesatisfactory. The water balancewas surplus ouput by calculated 550 mm of water storage in ground water (38,80%),outflowdistributed recharge river 622,21 mm(33,90%) regard to runoff including 24% (runoff coefficient 0,24)and evapotranspiration 504,8 mm (27,30%).